Kulturforskningens kvaliteter - Fornäs, Johan (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2008)
There is a widespread talk of an increasing role for culture and for transgressing borders, but still interdisciplinary cultural research experiences considerable difficulties in the new landscape of research policy. Having outlined the problematics of measuring quality in general terms a discussion and a series of proposals concerning the main dimensions of this problematics follows. First, the dominant scales for measuring publishing are criticised for being biased against the humanities, in that a too narrow set of international academic journals are unfairly favoured. Second, when external funding is measured, grants from the Swedish Research Council (Vetenskapsrådet) tend to overshadow all other and often equally important sources, including those from EU and the ESF (European Science Foundation). Third, it is argued that quality of education and of external communication should also be considered, as should the efforts made to create an innovative and productive environment in the institutional collective. Finally, particular attention is given to the specific issues relating to evaluating interdisciplinary applications, inspired by UK/US research by Georgina Born and others, as well as from a wide range of Swedish experiences that indicate that the disciplinary structure seriously hampers the ability to deal with truly interdisciplinary work. A list of necessary considerations is presented, proposing that such a list should be formulated and fine-tuned by the Swedish Research Council, and be anchored among all those who need to evaluate interdisciplinary work, so that such evaluation is correct and fair.